Geo-kinematic investigations in Slovakia and the region of Central and South- eastern Europe based on combination of permanent and epoch-wise GPS networks - HIPMANOVÁ, Linda (Contributions to Geophysics and Geodesy, 2009)
The region of Central and Southeastern Europe is covered by numerous GPS networks investigating geo-kinematical behavior of this area. These activities started in early nineties within the several projects as CERGOP and CERGOP-2/Environment. In this paper we describe the process of combination of four networks located in the region of Central and Southeastern Europe using the CATREF (Combination and Analysis of Terrestrial REFerence Frame) software developed in Institute Geographique National in France. We were particularly interested in the CEPER (Central European Permanent Network), CEGRN (Central European Geodynamic Reference Network), SGRN (Slovak Geodynamic Reference Network) and local network TATRY shortly described in this paper. Homogeneous velocity ﬁeld obtained from the ﬁnal combination is for the purpose of better interpretation divided into three parts: Central Europe, Slovakia and Tatra Mountains. Main interest is focused on the territory of Slovakia where the regional velocity ﬁeld is not so frequently discussed in scientiﬁc community as the case of Central and Southeastern Europe.